Insiders' Sales Under Rule 10b5-1 Plans and Meeting or Beating Earnings Expectations - Shon, John; Veliotis, Stanley (Management Science, 2013)
We find that firms with insider sales executed under Rule 10b5-1 plans exhibit a higher likelihood of meeting or beating analysts' earnings expectations (MBE). This relation between MBE and plan sales is more pronounced for the plan sales of chief executive officers (CEOs) and chief financial officers (CFOs) and is nonexistent for other key insiders. The market reactions to firms that successfully meet or beat expectations are relatively positive compared with their peers that fail to do so. One interpretation of our results is that CEOs and CFOs who sell under these plans may be more likely to engage in strategic behavior to meet or beat expectations in an effort to maximize their proceeds from plan sales. However, readers should exercise caution in making inferences, because the potential presence of limit order transactions makes it difficult to unambiguously determine the direction of causality of the relation we document. This paper was accepted by Mary Barth, accounting.